Shared voices from the classroom: Reflections on hybrid project-based learning in an academic writing course - Rochmahwati, Pryla; Yuliasri, Issy; Sukarno, Sukarno; Pratama, Hendi (Intelektual Pustaka Media Utama, 2024)
Hybrid project-based learning effectively develops academic writing skills in preparation for a gradual return to face-to-face instruction after a two-year pandemic triggered by Coronavirus Disease 2019 (COVID-19). Since this hybrid project-based learning initiative is a pioneering effort, it is essential to reflect on the program's successes and identify areas for improvement. This case study aims to explore the lecturers' and students' reflections on using hybrid project-based learning in academic writing courses. In-depth interviews and end-of-semester reflection were utilized to obtain data. Thematic analysis was conducted using the qualitative data analysis (QDA) miner lite software for data reduction. the findings revealed three prominent themes that emerged in this lecturers’ reflections: i) integrating varied learning modalities; ii) fostering critical thinking and involvement; and iii) improving competencies, as they were also crucial to boosting professional development. Meanwhile, students portray hybrid project-based learning as challenging and rewarding and fosters a sense of value and acceptability among students. This research has transformative implications for curriculum development and instructional practices in higher education, especially academic writing.